Pre-Service Biology Teachers’ Pedagogical Skills and Usability of Mobile Technology for Instructional Delivery During Teaching Practice - Bolanle Tawakalt-Anu Abdulazeez; Hameed Olalekan Bolaji; Adebayo Zakariyau Bello (Journal of Environmental and Science Education, 2024)
The ease of using mobile technology for teaching is hindered by deficiencies in teacher training programs. This study aims to address this issue and explore solutions for improving the use of mobile technology in teaching in Nigeria, particularly focusing on how pre-service science teachers can acquire pedagogical skills through mobile technology during teaching practice.Using a descriptive research method of the survey type, the study addresses five research questions and tests two research hypotheses at a significance level of 0.05. The population comprises science education students in public and private institutions in Ilorin, with samples drawn randomly from three colleges of education in different local government areas. A total of 285 respondents participated, providing data through a researcher-designed questionnaire titled "Pre-service Teachers’ Pedagogical Skills and Usability of Mobile Technology for Instructional Delivery Questionnaire (PTPSUMTIDQ)" Findings reveal a lack of technological literacy among classroom teachers in Nigeria, attributed to inadequate training. Mobile phones emerge as the most commonly used mobile technology device among teachers, and the study highlights the potential of mobile technology to help pre-service teachers acquire necessary pedagogical skills for successful careers in education. The paper recommends improving teacher training programs and providing education on the effective use of mobile technology to address these challenges.